Quantum Park Hotels: Can pipes break your reputation? - ZERRILLO, Philip (Institutional Knowledge at Singapore Management University, 2024)
The case of Quantum Park Hotels, a global hotel chain, is designed to uncover the challenges in designing a customer service recovery programme. The case is set in the Singapore branch of the hotel chain. General Manager David Ng is faced with several irate customers who have refused to pay their hotel bills, because they had no access to water from 4:30 am to 8:45 am that day due to damaged pipes. The front desk staff are seeking guidance from Ng on how to address the guest complaints. To help him arrive at a decision, Ng meets with his heads of guest services, finance, and loyalty programmes to get their insights and thoughts. Although the broken water pipes have since been repaired, they expect more customers to request some sort of compensation for their trouble. It will soon be check-out time at the hotel and while Ng is considering the inputs of multiple stakeholders, several decisions must be made. What sort of compensation should be offered — cash, room nights, hotel meals, or a combination of some or all of these? How much should be offered to the affected guests — a sum greater, less than or exactly the same as what they spent? Should different guests receive different benefits? And should something be done for guests who did not complain?